Evaluasi Penerapan Ferotrap dalam Mengendalikan Oryctes rhinoceros di Plasma dan Inti Kebun Brahma Bina Bakti - Desi Ropianti; Sulthon Parinduri (Jurnal Ragam Pengabdian, 2026)
This study evaluates the effectiveness of ferotrap application in controlling Oryctes rhinoceros in plasma and core areas of Brahma Bina Bakti Plantation, Muaro Jambi Regency, Jambi Province. The research was conducted from December 2025 to February 2026 using a descriptive quantitative method. Data were collected through direct observation of 10 ferotrap units in each location over 12 weeks. The parameters observed included the number of trapped O. rhinoceros, attack intensity, percentage of attacked plants, and level of plant damage. The results showed that ferotrap caught 308 O. rhinoceros in the plasma area and 420 in the core area. The highest attack intensity in plasma occurred in the third week (37.2%), while in the core area it occurred in the eighth week (41.2%). The percentage of attacked plants ranged from 40% to 80% in both locations. The damage level was predominantly at scores 0-2 (mild damage). Statistical analysis using Independent Sample t-test showed no significant difference between the number of catches in plasma and core areas (p-value = 0.271 > 0.05). These findings indicate that ferotrap is effective as a monitoring tool and can be used as a component of integrated pest management in oil palm plantations.